2019
DOI: 10.1039/c9cc03238j
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependent thermal stability of 2D gallenene

Abstract: Freestanding 2D metallic gallenene exhibits remarkable stability when the thickness is three atomic layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Interestingly, XPS indicates the stabilization of gallenene because the comparison of the Ga3d photoelectron peak for bulk Ga and gallenene indicates less oxidation (to a suboxide) for the gallenene layer compared to bulk Ga. This verified gallenene stability is consistent with recent work by Steenbergen and Gaston [86]. Microellipsometry has been used to measure, for the first time to the best of our knowledge, the optical spectra of epitaxial bilayer gallenene on the GaN(0001) and of the exfoliated hexagonal gallenene on Al 2 O 3 substrate and grapheme, as shown in Figure 13i.…”
Section: Polymorphism In 2d Gallenenesupporting
confidence: 89%
“…Interestingly, XPS indicates the stabilization of gallenene because the comparison of the Ga3d photoelectron peak for bulk Ga and gallenene indicates less oxidation (to a suboxide) for the gallenene layer compared to bulk Ga. This verified gallenene stability is consistent with recent work by Steenbergen and Gaston [86]. Microellipsometry has been used to measure, for the first time to the best of our knowledge, the optical spectra of epitaxial bilayer gallenene on the GaN(0001) and of the exfoliated hexagonal gallenene on Al 2 O 3 substrate and grapheme, as shown in Figure 13i.…”
Section: Polymorphism In 2d Gallenenesupporting
confidence: 89%
“…21,22 In contrast to this, 2D Ga is formed by cutting through covalently bound dimers, while maintaining metallic behaviour in plane. 20,23,24 Furthermore, in the bi-layer, (two atomic layers thick) this metallic character has been shown to be robust to signicant lattice strain and therefore is expected to persist even when supported by a wide range of substrate materials. 23 Due to 2D Ga having dangling covalent bonds, this material is able to bond covalently to a substrate material.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the tri-layer structure is thermodynamically stable to 306 K higher than the bi-layer structure. 24 Furthermore, studies centering around the liquid phase of bulk Ga have shown liquid-liquid phase transitions, [31][32][33][34][35] a tri-layered liquid structure at the free surface 36 and structural ordering at high pressure and temperature. 37 Ordering in 2D liquid phases has a long history.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Revealed by the first-principles simulation, freestanding bilayer gallenene is unstable and highly requires an underlying support, consistent with experimental results. However, as the layer numbers increased to 3, freestanding gallenene can still be stable when the temperature is about 100 K higher than the melting point of bulk Ga [67].…”
Section: Gallenenementioning
confidence: 99%